Increased Blood Pressure Variability Contributes to Worse Outcome After Intracerebral Hemorrhage: An Analysis of ATACH-2. Issue 8 (August 2018) - de Havenon, Adam; Majersik, Jennifer J.; Stoddard, Gregory; Wong, Ka-Ho; McNally, J. Scott; Smith, A. Gordon; Rost, Natalia S.; Tirschwell, David L.
Abstract : Background and Purpose—: Increased systolic blood pressure variability (BPV) is associated with worse outcome after acute ischemic stroke and may also have a negative impact after intracerebral hemorrhage. We sought to determine whether increased BPV was detrimental in the ATACH-2 (Antihypertensive Treatment of Acute Cerebral Hemorrhage II) trial. Methods—: The primary outcome of our study was a 3-month follow-up modified Rankin Scale of 3 to 6, and the secondary outcome was a utility-weighted modified Rankin Scale. We calculated blood pressure mean and variability using systolic blood pressure from the acute period (2–24 hours postrandomization) and subacute period (days 2, 3, and 7). Results—: The acute period included 913 patients and the subacute included 877. For 5 different statistical measures of systolic BPV, there was a consistent association between increased BPV and worse neurological outcome in both the acute and subacute periods. This association was not found for systolic blood pressure mean. Conclusions—: In this secondary analysis of ATACH-2, we show that increased systolic BPV is associated with worse long-term neurological outcome. Additional research is needed to find techniques that allow early identification of patients with an expected elevation of BPV and to study pharmacological or protocol-based approaches to minimize BPV.